2019
DOI: 10.2147/idr.s206295
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of two pheromone-responsive conjugative multiresistance plasmids carrying the novel mobile <em>optrA</em> locus from <em>Enterococcus faecalis</em></p>

Abstract: Background: The acquired optrA gene, which encodes a ribosomal protection protein of the ABC-F family, can confer cross-resistance to linezolid and florfenicol, posing a serious therapeutic challenge to both human and veterinary medicine. Purpose: The objective of this study was to investigate the two Enterococcus faecalis ( E. faecalis ) plasmids for their fine structure, their transferability and the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The gene cfr was initially found on the 17.1-kb plasmid pSCFS1 from an S. sciuri isolate and was shown to encode an rRNA methylase mediating resistance to phenicol by methylation of the 23S rRNA. In contrast, the gene fexA , which encodes an efflux protein within the major facilitator superfamily (MFS), was first identified on the 34-kb plasmid pSCFS2 [ 17 ] from S. lentus and was shown to be part of the Tn 554 -like transposon Tn 558 [ 18 ]. fexB , also a phenicol exporter gene, was first identified on the pEFM-1 (35 kb in size) of E. faecium and pEH-1 (25.3 kb in size) of E. hirae , both strains with swine origins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gene cfr was initially found on the 17.1-kb plasmid pSCFS1 from an S. sciuri isolate and was shown to encode an rRNA methylase mediating resistance to phenicol by methylation of the 23S rRNA. In contrast, the gene fexA , which encodes an efflux protein within the major facilitator superfamily (MFS), was first identified on the 34-kb plasmid pSCFS2 [ 17 ] from S. lentus and was shown to be part of the Tn 554 -like transposon Tn 558 [ 18 ]. fexB , also a phenicol exporter gene, was first identified on the pEFM-1 (35 kb in size) of E. faecium and pEH-1 (25.3 kb in size) of E. hirae , both strains with swine origins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids with such gene organization have not been reported previously from any optrA -carrying E. faecalis isolates. While there has been one report of two pheromone-responsive plasmids carrying optrA in E. faecalis (30), both plasmids were identified in E. faecalis isolates from pigs, with only one of them (pE508) containing a single sex pheromone gene ( prgB ) based on full plasmid genome sequencing. Fourth, our plasmid typing studies demonstrated, for the first time, the abundant presence of rep 9 -type plasmids (prototype pCF10) in optrA -carrying E. faecalis clinical isolates (17/26 or 65%, Table 1), implying a high prevalence of sex pheromone plasmids in clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there have been reports of easy transfer of optrA -carrying plasmids in vitro between E. faecalis and E. faecium (13) and between human- and pig-derived E. faecalis (30). Our previous transcriptomics (31) and proteomics (32) analyses of a linezolid-resistant E. faecalis strain P10748 consistently revealed a significant co-upregulation of optrA gene with several genes involved in mating and pheromone response, implying a localization of this gene in a sex pheromone plasmid allowing highly efficient resistance transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Genomics has provided critical insights into the genetic relatedness of resistant strains, the structure of MGEs and their role in the mobilization of linezolid resistance determinants. Examples include: an analysis of optrA -carrying plasmids from E. faecalis , which found optrA flanked by two active copies of IS 1216 that can facilitate its spread ( Shang et al, 2019 ); the widespread identification of optrA located in a Tn 6674 -like element in E. faecalis isolated from different countries and sources ( Freitas et al, 2020b ); IS 1216E elements that have been shown to mediate the insertion of poxtA into a pT-E1077-31 plasmid in E. faecium ( Shan et al, 2020 ); while in MRSA, a Tn 6349 composite transposon carrying both poxtA and cfr was found to possess a modular structure consisting of fragments from other previously described MGEs ( D’Andrea et al, 2019 ). The presence of these MGEs in cfr , poxtA , and optrA carrying multi-resistance plasmids likely aids in the persistence and dissemination of linezolid resistance genes among these Gram-positive pathogens.…”
Section: Linezolid Resistancementioning
confidence: 99%